THE INFLUENCE OF RISK GOVERNANCE ON THE PROFITABILITY OF REGIONAL GOVERNMENT-OWNED GENERAL BANKS IN INDONESIA BEFORE AND DURING THE COVID-19 PANDEMIC - Tri Reswanti; Harjum Muharram (RADJA PUBLIKA, 2025)
In the face of global uncertainty such as the Covid-19 pandemic, the resilience of the banking system becomes a strategic issue, especially for regional government-owned commercial banks that have an important role in regional economic stability. This study aims to examine the effect of risk disclosure, the number of risk monitoring committees, and risk committee activities on bank profitability as measured by Return on Assets (ROA) and Return on Equity (ROE), and to test the differences using the paired sample t-test method for each variable before and during the Covid-19 pandemic. This research method uses a quantitative approach. Hypotheses H1–H6 are tested by regression, while hypotheses H7a–H7e are tested by paired sample t-test. The results of the first regression show that only H1 is accepted, namely risk disclosure has a significant positive effect on ROA (t = 2.525; p = 0.013). However, H2 and H3 are rejected because the Number of Risk Committees and risk committee activities do not have a significant effect on ROA (t = -1.741; p = 0.084 and t = -1.923; p = 0.056). The first regression model has a determination value (R²) of 0.078, which means that 7.8% of the variation in ROA can be explained by the independent variables. The second regression shows that only H5 is accepted, namely the number of risk committees has a significant positive effect on ROE (t = 2.019; p = 0.045). While H4 and H6 are rejected because risk disclosure and risk committee activities do not have a significant effect on ROE (t = -0.920; p = 0.359 and t = -1.695; p = 0.092). The determination value (R²) of 0.055 indicates that 5.5% of the variation in ROE is explained by the model. Furthermore, the results of the paired sample t-test showed that only H7c, H7d, and H7e were accepted. Risk committee activity increased significantly during the pandemic (t = -2.048; p = 0.044), and there was a significant decrease in ROA during the Covid-19 pandemic (t = 3.446; p = 0.001) and ROE (t = 4.920; p = 0.000). Meanwhile, H7a and H7b were rejected because risk disclosure (t = -1.000; p = 0.320) and the number of risk committees (t = -1.211; p = 0.230) did not experience significant differences before and during the Covid-19 pandemic. This study provides evidence that risk disclosure and the number of risk monitoring committees contribute to explaining bank profitability, although in general the explained variation is relatively small. This finding highlights the importance of improving the quality of risk governance that is more adaptive in responding to the crisis.